GERAK SEHAT: PENDAMPINGAN KEBUGARAN ANAK TUNAGRAHITA DI LINGKUNGAN SLB YAYASAN PUTRA PANCASILA - Khotimah, Khusnul; Ary Artanty; Ahmad Junaidi; Luthfie Lufthansa; Alfian Yahya; Paulus Rah Adi Pawitra; Laila Nur Rohmah (CV SWA Anugerah, 2024)
Physical fitness is an essential component in supporting the development of children, including those with intellectual disabilities (ID), who face challenges in motor skills and cognitive abilities. The “Healthy Movement” program aims to partisipasi the physical and motor skills of children with Intellectual Disabiity through guided adaptive physical activities in a school setting. This program employs a participatory approach involving teacher, parents and program facilitators. The activities were implemented in three phases: planning, execution and evaluation. Physical activites included simple game, rhytmic movement and basic motor exercises tailored to the needs of children with Intellectual Disability. Data were colected through observation, fitnest test, interviews and documentation and analyzed descriptively. The results revealed significant improvements in balance, coordination and muscle strenght among children with Intellectual Disability. Additionally, the children exhibited increased confidence and enthusiasm in participating in the activities. Teachers and parent gained new insights into the importance of physical fitness and effective strategies for guiding chidren with Intellectual Disability. This program successfully created positive impact on children with Intellectual Disability and raised awareness of the impportance of physical fitness in supporting their well-being. The program’s sustainabillity is ensured through the integration of the “Healthy Movement” module into the physical education curriculum at schools.